2021
DOI: 10.3389/fpsyg.2021.628350
|View full text |Cite
|
Sign up to set email alerts
|

How Do We Perceive a Humorous Manager? Manager Humor, Impression Management, and Employee Willingness to Work With the Manager

Abstract: Humor is a form of communication that is intended to be entertaining and produce positive affective and cognitive responses from receivers. Nonetheless, humor in the workplace is a complicated matter. It has been recognized as a valuable tool for managers because it can activate various favorable outcomes and alter employees’ perception of the manager’s warmth and competence (impression management), but not always to the benefit of the manager. In our studies, the use of humor showed changed attitudes toward a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 145 publications
(248 reference statements)
0
6
0
Order By: Relevance
“…Finally, in the fourth theme, researchers in marketing explored the effect on brands (e.g., Brender-Ilan and Reizer, 2021 ), country stereotypes ( Grigoryev et al, 2019 ; Barbarossa and Mandler, 2020 ; Feng et al, 2023 ; Rojas-Mendez and Davies, 2023 ), perception of providers in front-line service ( Güntürkün et al, 2020 ; Leung et al, 2020 ), the effect of the two traits on consumers’ prosocial behavior ( Liu and Lin, 2018 ; Zhou et al, 2019 ; Chua et al, 2023 ), perception of endorsers in marketing communications ( Bauer et al, 2022 ; Linne et al, 2022 ; Philipp-Muller et al, 2023 ), and perception of AI ( Belanche et al, 2021 ; Borau et al, 2021 ; Yoganathan et al, 2021 ). To summarize the main themes, providing a visual answer to our first research question, Figure 4 provides a graphic summary of the different topics and research streams identified during this review ( Figure 9 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, in the fourth theme, researchers in marketing explored the effect on brands (e.g., Brender-Ilan and Reizer, 2021 ), country stereotypes ( Grigoryev et al, 2019 ; Barbarossa and Mandler, 2020 ; Feng et al, 2023 ; Rojas-Mendez and Davies, 2023 ), perception of providers in front-line service ( Güntürkün et al, 2020 ; Leung et al, 2020 ), the effect of the two traits on consumers’ prosocial behavior ( Liu and Lin, 2018 ; Zhou et al, 2019 ; Chua et al, 2023 ), perception of endorsers in marketing communications ( Bauer et al, 2022 ; Linne et al, 2022 ; Philipp-Muller et al, 2023 ), and perception of AI ( Belanche et al, 2021 ; Borau et al, 2021 ; Yoganathan et al, 2021 ). To summarize the main themes, providing a visual answer to our first research question, Figure 4 provides a graphic summary of the different topics and research streams identified during this review ( Figure 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…These associations might change among different consumers (e.g., based on demographics), and due to the interaction with other variables, such as the use of humor ( Brender-Ilan and Reizer, 2021 ; Howe et al, 2023 ) or emoticons when communicating the brand ( Ivens et al, 2015 ). Other studies examined the interaction of W/C with the type of narration used to present the brand (i.e., in first vs. third person) ( Chang et al, 2019 ).…”
Section: Themes From Bibliographic Couplingmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies show humor production ability is related to verbal intelligence [16,17], and the use of humor signals confidence, however, the inappropriate use of humor signals incompetence [8]. There is recent evidence to suggest humor use only affects emotional connection (warmth) rather than judgement on competence [18]. Despite the inconsistent findings, these studies suggest effective humor use may involve both cognitive and emotional intelligence.…”
Section: •Mark Twainmentioning
confidence: 92%
“…In the therapeutic relationship, humour has been shown to improve communication with the patient and the coping with difficult situations, helping to create a climate of trust and confidence (Birkelund & Larsen, 2013 ; Haydon & van der Riet, 2014 ; Leñero, 2015 ; Sousa et al, 2019 ). In the work environment, it improves the working atmosphere, favours relationships between colleagues, promotes teamwork, increases motivation and job satisfaction and reduces job burnout and stress, resulting in a higher quality of care (Bartzik et al, 2021 ; Brender‐Ilan & Reizer, 2021 ; Chen & Ayoun, 2019 ; Cheng et al, 2021 ; Mesmer‐Magnus et al, 2018 ; Vaz de Almeida & Nunes Health, 2020 ).…”
Section: Introductionmentioning
confidence: 99%